Research on Users’ Willingness to Use the Urban Subway Wayfinding Signage System Based on the DeLone & McLean Model Theory: A Case Study of Wuxi Subway - Kun Wang; Chuhao Shen; Mingxin Li; Jianing Li (Systems)
This study, which is grounded in the information systems success model (D&M model) proposed by Delone and Mclean, investigates user satisfaction and the intention to continue using the urban subway signage system; Wuxi subway is taken as a case study. Through a questionnaire survey, the research integrates elements from the D&M theory, such as information quality, system quality, service quality, user satisfaction, and intention to use. The data were collected using a combination of online and offline survey methods and were analyzed using IBM SPSS 23 and AMOS 23. The findings reveal that system quality serves as a crucial driver of user satisfaction, while service quality exerts the most significant influence on users’ intention to use. Additionally, information quality is equally important. The optimization suggestions encompass the need to ensure the relevance, completeness, timeliness, and accuracy of information; enhance the usability and reliability of the system; and bolster the responsiveness, empathy, and tangibles of the service. These discoveries provide a scientific basis and practical guidance for optimizing the signage systems of Wuxi subway and other urban public transportation systems, with the aim of elevating passengers’ intention to use and their satisfaction.